A Kinetic Explanation for Combined Potassium Gains and Radiogenic 40Argon Losses of Diagenetic Illite-Rich Clay Separates - Norbert Clauer; Abraham Lerman (Geosciences, 2022)
In this study, a kinetic model sketches the concomitant K gain and radiogenic 40Ar loss of clay separates recovered from progressively buried sediments. Published K-Ar ages of clay separates from the Mahakam Delta, the Texas Gulf Coast, and the North Sea were used to constrain the modeling. As compared with analytical results, the model simulates changes relative to depth or to deposition time of the K-Ar ages from fine- and coarse-grained clay crystals. The decrease in the K-Ar ages of detrital-rich coarse-grained fractions (>2 μm) is bracketed with depth by K addition rates between 0.2 and 3.5%/Ma and slightly higher 40Ar release rates between 0.5 and 4.5%/Ma. The former rate varies from 3.5 to 6%/Ma in the fine-grained fractions (<0.4 μm) and the latter rate varies from 0.7 to 6%/Ma in the same fractions. In fact, the K addition and the radiogenic 40Ar release rates record independent processes on different material sizes and types. Small K addition and 40Ar escape rates of about 1%/Ma also simulate analytical cases in which the mean K-Ar ages of the finer grained fractions remain about constant with increasing depth, confirming that the relationship between K-Ar age and stratigraphic depth cannot represent a temporary “steady state”, but a continuing dynamic process at a smaller rate. In turn, the modeled results help quantifying the illitization reactions in size separates consisting of authigenic and detrital clay materials from sediments covering stratigraphic intervals from 10 to 1000 Ma.